Protective Effects of Curcumin against Iron-induced Toxicity - Moinipour, Nastaran; Barati, Mahdi; Sahebkar, Amirhossein; Iranshahy, Milad; Shakeri, Abolfazl (Current Pharmaceutical Biotechnology, 2022)
Iron is an essential element in cellular metabolism that participates in many biochemical reactions. Nevertheless, iron overload in the body is the cause of damage in some organs including the liver, glands, brain, heart, gastrointestinal tract and lung. Iron chelation therapy could be considered an effective approach for removing excess iron. Deferoxamine, deferiprone and deferasirox are three common iron chelators in clinical practice but cause several side effects. In this context, the use of curcumin, a dietary phytochemical derived from turmeric, as a natural and safe antioxidant with iron-chelating activity may be a useful strategy for the management of iron overload. This review focuses on the deleterious effect of iron accumulation in different organs of the body as well as the therapeutic potential of curcumin against iron-induced toxicity.
Keywords: toxicity